When guanxi meets connectivity: The underlying mechanisms of young adults' participation in micro-charity. Issue 1 (4th October 2017) - Lin, Xun; Huang, Hua
Abstract : Purpose: The purpose of this paper is to reveal the underlying mechanisms that drive young adults' participation in micro-charity. Design/methodology/approach: A case study, which formed a large online ethnographic project, was conducted in which the twin methods of participatory observation and in-depth interviews were used to access the experience of a selected group ( n = 60) of college students. Findings: The present paper identifies that young adults' participation in micro-charity is mainly driven by three underlying mechanisms: the formation of a powerful environment for the distribution of awareness of obligation, creation of trust towards others in distant or weak ties and symbolic construction of collective identity with a shared commitment. Originality/value: This paper is an exploratory work which sheds new light on charity or other social entrepreneurship development in the social media era. Specifically, the connectivity of social media and the pre-existing relationships may work well together and lead to many positive outputs, including distributing awareness of social obligation, instilling social trust and strengthening social coherence.